Analisis Penerapan Green Accounting, Profitabilitas Dan Pengungkapan Corporate Social Responsibility Terhadap Kinerja Keuangan - An Nisa Mamluatul Karomah Alfindi; Nursiam Nursiam (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to analyze the application of green accounting, profitability and disclosure of corporate social responsibility to financial performance. The approach used in the research is quantitative research. The population used in this study is manufacturing companies listed on the Indonesia Stock Exchange for the period 2019 - 2022. Researchers used a sampling technique in the form of purposive sampling so that a total sample of 89 data was obtained. The data analysis methods used in this study are descriptive statistical analysis, classical assumption test, multiple linear regression test and hypothesis testing using SPSS version 23. The results provide evidence that green accounting¸ and corporate social responsibility have no effect on financial performance, while profitability affects financial performance